Programa BH em férias: os desafios de uma política intersetorial e os saberes dos profissionais - Lucilene Alencar das Dores (2016)
The Program in Belo Horizonte City, called BH em Férias (PBF) is an intersectorial Program developed by the Municipal Social Politics Secretary (SMPS) in association with other departments and foundations in order to provide to the communities, during the period of school vacations, leisure activities that include cultural experiences in games and jokes, sports and arts. The Program runs for one week of January and July in the Reference Centers Social Assistance, called CRAS. Other spaces - parks, museums, zoo and private institutions, all of them as partners of the City - are used as complementary sites for the development of Program activities. In this space called CRAS, professionals working in the Program have minimal training in higher education with training in social work, physical education and psychology. The construction of professional knowledge are the result of scientificknowledge, considered those acquired by the processes of academic as well as technical knowledge of the action knowledge, as those skills gained in life experience , both professional and social relationships. The objective of this study is to analyze how the constitution of professional knowledge operating in PBF is. Therefore, I propose to understand how the process of intersectoriality, caused by the structure of Municipal Politicand PBF, interferes in the division of knowledge among professionals with different backgrounds; identify shared knowledge among analysts and the relationship of this knowledge with the performance of the professional in the Program; and also understand how professionals articulate the knowledge of academic training and experience to work withrecreation. The methodological choices of this study sought to show the reality from the operation of a single territory covered PBF. This cut allowed to understand the specifics training and professional performances. For investigation I combined reading procedures ofofficial documents of the Program and researches. Data analysis allowed me to identify that whatever vocational training is in social work, physical education and psychology, it was possible to realize that the academic interferes with professional work processes since they resort to scientific training to present their views on the leisure and how formulate actionstrategies in the PBF. Moreover, the experiences in the workplace, family and social relationships are crucial to dealing with professional problems considering that these experiences make it possible to build knowledge from the encounter with the other. We understand that intersectorial organization of PBF presents difficulties of collective planning and co-responsibility between the sectors involved, which results in the context of dynamic practice that tend address the weaknesses of the political structure. The division of administrative and operational knowledge among professionals are needed and take up much of the time, making the exchange of knowledge that allow reframe the work of professionals.